Evaluasi Penggunaan Obat Antihipertensi pada Pasien Geriatri Rawat Inap di RSUD Karanganyar dengan Metode ATC/DDD - Ivonia Odi Seran; Kisrini Kisrini; Pudiastuti Pudiastuti (Jurnal Farmasi Indonesia, 2014)
Hypertension is a major health problem most frequently found in Indonesia. This disease can affect anyone from various socio-economic groups. This study aimed to determine the drug utilization in terms of the drug classes, dosage form, drug administration route (pattern of antihypertensive drugs usage) in geriatric patients and its compliance with the Medical Care Standards (MCS) and the Hospital Formulary at Karanganyar Hospital in 2011 using the ATC / DDD methods, and determine antihypertensive drugs which include in DU90% segment. This study used secondary data which were taken from the patient's Medical Record. This research was quantitative descriptive research, the data were collected retrospectively. Data of antihypertensive utilization and inpatient visit obtained from Medical Record Installation. Entire data then were processed to determine the quantity of antihypertensive utilization in DDD/100 unit of inpatient day and Drug Utilization profile (DU90%). The results showed that the antihypertensive drugs utilization in geriatric patients (60 years and above) in Karanganyar Hospital during 2011 were captopril (60.69%), furosemide (11.26%), amlodipine (8.17%), nifedipine (9.45%), hirdroklorotiazid (5.94%), lisinopril (3.44%), bisoprolol (1.05%), and from the DU90% table, drugs which include in the DU90% segment were captopril, furosemide, and amlodipine. The compliance to Hospital Formulary in 2011 was 80%.